ANALISIS TINGKAT KEMATANGAN (MATURITY LEVELS) UNIT LAYANAN PENGADAAN KABUPATEN BADUNG - Darmapramita, I Gde Uma; Salain, I M. Alit K.; Nadiasa, Mayun (JURNAL SPEKTRAN, 2015)
The implementation of government procurement of goods and service is governed by presidential regulation number 70 year of 2012.  According to that, in Badung Regency implemented centralized in Procurement Service Unit of Badung Regency. As the one of Indonesia procurement unit pilot, Procurement Service Unit of Badung Regency has given the opportunity to perform a self assessment of its  maturity levels as government unit. The objective of this research is to find factors that influence Procuremet Service Unit of Badung Regency maturity levels, and also to find out in what level is Procurement Service Unit of Badung Regency stand. Data collection for this research have done by  using questionnaire that involve 50 respondents who understand very well about the duties and function of Procurement Service Unit of Badung Regency to perform a government procurement of good and services. The data analysis have been performed by use of factor analysis and supported by SPSS program. The result shows there are 3 factors that influent the Procurement Service Unit of Badung Regency maturity levels, which are : the synergy and organization culture, resources and risk management and organization’s performance development.  Whereas the maturity levels of Procurement Service Unit of Badung Regency is stand at compliance. Based to the factors that formed, the highly commitment and strong leadership of Badung Regency leader are very decisive to push ahead the enhancement  and  the development of Procurement Service Unit of Badung Regency.  First thing can be done is to establish an independent Procurement Service Unit therewith its Procurement Unit Development road maps that can be tiered and sustainable plan, monitor and evaluate
Keywords: procuremet service unit, maturity levels, analysis factor.